PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN EMPLOYEE ENGAGEMENT TERHADAP EMPLOYEE PERFORMANCE DENGAN ORGANIZATIONAL COMMITMENT SEBAGAI VARIABEL MODERASI PADA DINAS SOSIAL PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK KABUPATEN TANAH DATAR - Noferdi, Albert; Heliyani, Heliyani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to see the influence of influences organizational citizenship behavior (OCB) and employee engagement to employee performance with organizational commitment as a moderating variable at the Social Service for Women's Empowerment and Child Protection of Tanah Datar Regency. The sample in this study was 31 civil servants at the Department of Social Services for the Empowerment of Women and Child Protection, with the sampling technique used in this study being the total sampling technique. The data analysis method used in this study is the Structural Equation Modeling (SEM) analysis technique based on the Partial Least Square (PLS) variant. Research data collection was carried out through interviews and questionnaires. The results of the study indicate that the organizational citizenship behavior variable has a positive and significant influence on the employee performance variable and the employee engagement variable also has a positive and significant influence on the employee performance variable at the Social Service for Women's Empowerment and Child Protection of Tanah Datar Regency. Likewise, the organizational commitment variable also has a positive and significant influence on the employee performance variable. From the moderating variables used, namely the organizational commitment variable, it can be seen that the organizational commitment variable is not able to strengthen the influence of organizational citizenship behavior on the employee performance variable, as well as on other variables that organizational commitment is not able to strengthen the influence of employee engagement on the employee performance variable at the Social Service for Women's Empowerment and Child Protection of Tanah Datar Regency. Keywords: Organizational Citizenship Behavior, Employee Engagement, Organizational Commitment and Employee Performance